Método destructivo de baja intensidad para la generación de modelos alométricos a nivel de grupos de especies y tipo de bosque para el estrato bosque seco pluvioestacional del Ecuador. - Prieto Ramón, Marcelo Xavier (2014)
Conduct studies on the generation of statistically validated allometric models, to quantify the total aboveground biomass and total aboveground carbon content at species groups level and forest stratum, in the pluviseasonal dry forests of Ecuador. Enables you to provide the necessary knowledge to plan the management and conservation of forests. In this context the objectives that led to the realization of the present research were to generate allometric models of the aboveground biomass, for species groups and from strata of Ecuador's pluviseasonal dry forest and dissemination of the achieved results. The species inventory was conducted in a total of 12 sampling units that cover an area of 4.32 ha, in sites as Mangahurco, Loja; Farms, El Oro; Mamey, Guayas; and Piñas del Julcuy, Manabí; each sampling unit was 60 m x 60 m, separated into three girdles; in the first girdle all individuals with DBH ≥ 10 cm were measured, in the girdles’ two and three, individuals ≥ 20 cm were measured; the dasometric parameters (DBH, HT, HC, DC, and density) were measured; in the species identification we had a botanical and samples were also collected that were taken to Loja Herbarium. For allometric models by species groups, the following classes of densities were considered (< 0,5 Kg/m3; from 0,51 Kg/m3 to 0,7 Kg/m3; y, > 0,71 Kg/m3) and morphology classes (species with commercial bole <3 m tall, 3.01 m ≥ 7 m tall , and> 7.01 m tall); for each individual. Were recorded in a total of 633 individuals, which were grouped into 9 groups of species for developing allometric models with the help of InfoStat software; for the 9 groups of species that were determined and, for stratum pluviseasonal dry forest of Ecuador, the models were obtained from 20 statistical relationships for each species group and stratum, where the following parameters were considered for its validation (R2, R2 adjusted, AIC, BIC, p-value ≤ 0.05). The models can be used in similar conditions to those of the present investigation to estimate total aboveground biomass conditions reliably